Beginning iOS 5 Development Exploring the iOS SDK - Mark, David; Nutting, Jack.; LaMarche, Jeff.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
The team that brought you the bestselling Beginning iPhone 4 Development is back again for Beginning iOS 5 Development, bringing this definitive guide up-to-date with Apple's latest and greatest iOS SDK, as well as with the latest version of Xcode.  There's coverage of brand new technologies, with chapters on storyboards and iCloud, for example, as well as significant updates to existing chapters to bring them in line with all the changes that came with the iOS 5 SDK. You'll have everything you need to create your very own apps for the latest iOS devices, including the iPhone 4S, iPad 2, and the latest iPod touch. Every single sample program in the book has been rebuilt from scratch using Xcode 4.2 and the latest iOS 5-specific project templates and designed to take advantage of the latest Xcode features. Assuming only a minimal working knowledge of Objective-C, and written in a friendly, easy-to-follow style, Beginning iOS 5 Development offers a complete soup-to-nuts course in iPhone, iPad, and iPod touch programming. The book starts with the basics, walking through the process of downloading and installing Xcode and the iOS 5 SDK, and then guides you though the creation of your first simple application. From there, you'll learn how to integrate all the interface elements Apple touch users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders. You'll master a variety of design patterns, from the simplest single view to complex hierarchical drill-downs. The confusing art of table building will be demystified, and you'll learn how to save your data using the iPhone file system. You'll also learn how to save and retrieve your data using a variety of persistence techniques, including Core Data and SQLite. And there's much more! You'll learn to draw using Quartz 2D and OpenGL ES, add multitouch gestural support (pinches and swipes) to your applications, and work with the camera, photo library, accelerometer, and built-in GPS. You'll discover the fine points of application preferences and learn how to localize your apps for multiple languages. The iOS 5 update to the bestselling and most recommended book for Cocoa touch developers Packed full of tricks, techniques, and enthusiasm for the new SDK from a developer perspective Written in an accessible, easy-to-follow style.
Keywords: Apple computer; Application software; Apple and iOS; Computer Applications